Respuesta :

Answer:

3

Step-by-step explanation:

system of equations:

[tex]a+b=4[/tex]

[tex]a^3+b^3=28[/tex]

[tex]a=4-b[/tex]

plug in for a in other equation and solve

[tex](4-b)^3+b^3=28[/tex]

[tex]64-48b+12b^2-b^3+b^3=28[/tex]

[tex]64-48b+12b^2=28[/tex]

[tex]0=36-48b+12b^2[/tex]

[tex]0=3-4b+b^2[/tex]

[tex]0=(b-3)(b-1)[/tex]

[tex]b = 3[/tex]

or

[tex]b=1[/tex]

plug into other equation to get a

[tex]a=4-b=4-3=1[/tex]

or

[tex]a=4-b=4-1=3[/tex]

multiply together

[tex]1*3=3[/tex]